PSYCHOLOGICAL DISTRESS AND COMORBID PHYSICAL CONDITIONS: DISEASE OR DISABILITY?. Issue 6 (6th August 2013) - Byles, Julie E.; Robinson, Ian; Banks, Emily; Gibson, Richard; Leigh, Lucy; Rodgers, Bryan; Curryer, Cassie; Jorm, Louisa
<x xml:space="preserve">Abstract</x> Background The relationship between comorbidity and psychological distress is well documented, however the mechanism of this association is unclear. We aim to assess the extent to which the association between common chronic conditions and high scores on the Kessler Psychological Distress Scale (K10) measure of psychological distress vary according to comorbid conditions, disability, and sociodemographic circumstances. Methods Analysis of self‐reported cross‐sectional data from the New South Wales 45 and Up Study, Australia, for 236, 508 participants aged 45 years and over, using logistic regression modeling. Results Self‐reported heart attack/angina, other heart disease, stroke, and diabetes were all significantly associated with higher risk of high/very high K10 scores. These associations were attenuated, but remained statistically significant, when comorbidity, disability, and sociodemographic factors were added to the model. Men reporting needing help for daily tasks were nine times as likely to report high/very high K10 scores as those without this need, and women reporting needing help were seven times more likely to have high/very high K10 scores. Conclusions Heart attack/angina, other heart disease, stroke, and diabetes are all significantly associated with psychological distress. However, these effects are partly explained by other comorbid conditions, limitations on physical functioning, and sociodemographic factors. These findings highlight the importance of developing public health policies that encompass psychological, physiological, and social domains, and provide crucial insights for clinicians in identifying and supporting those people at risk of psychological distress.